High-performance macromolecular data delivery and visualization for the web - Sehnal, David; Svobodová, Radka; Berka, Karel; Rose, Alexander S; Burley, Stephen K; Velankar, Sameer; Koča, Jaroslav (Acta crystallographica. Section D, Structural biology, 2020)
Biomacromolecular structural data make up a vital and crucial scientific resource that has grown not only in terms of its amount but also in its size and complexity. Furthermore, these data are accompanied by large and increasing amounts of experimental data. Additionally, the macromolecular data are enriched with value-added annotations describing their biological, physicochemical and structural properties. Today, the scientific community requires fast and fully interactive web visualization to exploit this complex structural information. This article provides a survey of the available cutting-edge web services that address this challenge. Specifically, it focuses on data-delivery problems, discusses the visualization of a single structure, including experimental data and annotations, and concludes with a focus on the results of molecular-dynamics simulations and the visualization of structural ensembles.
Keywords: uživatelské rozhraní počítače; Software; software; Computer Graphics; web-based; data delivery; internet; macromolecules; Internet; Macromolecular Substances; User-Computer Interface; makromolekulární látky; visualization; browser-based; počítačová grafika